2018
DOI: 10.1007/s11856-018-1778-x
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of BMO in terms of endpoint bounds for commutators of singular integrals

Abstract: We provide a characterization of BMO in terms of endpoint boundedness of commutators of singular integrals. In particular, in one dimension, we show that b BMO ≂ B, where B is the best constant in the endpoint L log L modular estimate for the commutator [H, b]. We provide a similar characterization of the space BMO in terms of endpoint boundedness of higher order commutators of the Hilbert transform. In higher dimension we give the corresponding characterization of BMO in terms of the first order commutators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…It is well-known that the commutator of the Hilbert transform has the following properties: a) [ For more details, we refer to the references listed above. We also point out that there are quite a number of recent results on the characterisations of commutators in the above forms for singular integrals in different settings, see for example [10,22,9,21,25,24,15,19,13,8,1]. Inspired by these classical results above, it is natural to ask whether these results hold on the Heisenberg group H n .…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It is well-known that the commutator of the Hilbert transform has the following properties: a) [ For more details, we refer to the references listed above. We also point out that there are quite a number of recent results on the characterisations of commutators in the above forms for singular integrals in different settings, see for example [10,22,9,21,25,24,15,19,13,8,1]. Inspired by these classical results above, it is natural to ask whether these results hold on the Heisenberg group H n .…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 85%
“…We also point out that this endpoint characterisation in Theorem 1.3 above is sharp since following the method in [24] in the Euclidean setting and using the lower bound in Theorem 1.1, it is easy to construct a function b ∈ BMO(G) such that [b, R j ] fails to be weak type (1,1).…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Observe that (1.4) contains as a particular case the endpoint estimate obtained in [14] and provides precise quantitative bound for the case in which the symbol has better local decay properties than BM O functions. We recall that in [1], it was shown that if a commutator of a certain singular integral satisfies a weak-type (1, 1) estimate then b ∈ L ∞ and that the L log L estimate, first settled in [31], implies that b ∈ BM O. Bearing those results in mind we wonder whether b ∈ Osc exp L r should be a neccesary condition for (1.4), at least in the case u = 1, to hold.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Very recently we have learned that after finishing this paper some results concerning the necessity of BM O for the endpoint estimate of commutators have been obtained. We remit the interested reader to [1,9] for those results. In an even more recent work [14], a more general version of the second part of Theorem 1.1 has been obtained, answering positively a question posed in Remark 4.1.…”
Section: Remarks and Complementsmentioning
confidence: 96%